STRATEGI KOMUNIKASI SALES DALAM MENINGKATKAN PENJUALAN CITY HATCHBACK RS DI MASA PANDEMI COVID-19 (STUDI PADA DEALER HONDA PONDOK PINANG) - Nur Adha Alfaizi (2022)
The COVID-19 pandemic that occurred caused a decrease in the pace of the economy that hit Indonesia. It leads to the reduction in people's purchasing power. Based on data reports from the Association of Indonesian Automotive Industries (Gaikindo) there was a significant decrease in sales in 2019 and 2020. Businessmen are required to be able to adjust to current conditions while continuing to make creative innovations. PT. Honda Prospect Motor introduces its newest product, the Honda City Hatchback RS. This study addresses problems related to the sales communication strategy of Honda Pondok Pinang in increasing sales of City Hatcback RS. It is hoped that it can increase sales through marketing communication strategies. This study uses a qualitative research method using primary data from interviews and secondary data from documentation and observation. Based on the research results, sellers use the STOP-SIT analysis strategy. STOP-SIT analysis is a strategy used by sales by utilizing media as tools. Instagram, website, Facebook, and WhatsApp are media used by sellers to promote products and find consumers. Sellers are guided by supervisors in developing strategic planning/planning to strategy implementation and strategy evaluation. This the STOP-SIT strategy has a very important role in increasing sales.